A New Buck-Boost Converter Configuration Reducing Current Stress on the Switch: VERSION OF RECORD ONLINE: 18/09/2025 - Van Ban Nguyen; Thanh Hai Quach; Viet Anh Truong; Vo Hong Nghi Pham (Journal of Technical Education Science, 2025)
This paper presents a novel configuration for a DC buck-boost converter that mitigates current stress from inductors and capacitors on the switches during conduction states. Steady-state analysis, ripple current, voltage stress, and power loss evaluations have been conducted. Simulation and analytical results in buck and boost modes reveal that the proposed converter exhibits very low ideal load current overshoot for switches S1, S2, and diodes D1 and D2, even when the conversion ratio ranges from 0.2 to 2. This performance surpasses SEPIC and other analyzed configurations, contributing to reduced power losses and improved overall efficiency. Furthermore, performance experiments, including the impact of parasitic resistances, confirm that the proposed converter achieves the highest efficiency compared to other converters. These results demonstrate superior performance, reduced power losses, and extended lifespan, making the converter an optimal solution for power electronics and electrical applications. In addition, the converter features continuous input and output currents, making it particularly suitable for renewable energy applications such as photovoltaic systems, battery energy storage, and microgrid systems, where current continuity is essential for enhancing system stability and minimizing electromagnetic interference.